2004
DOI: 10.1103/physrevlett.93.157201
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Ordering in Lithium and an Upper Limit on its Ambient Pressure Superconducting Transition Temperature

Abstract: We have discovered spontaneous ordering of nuclear spins in lithium metal by NMR measurements at very low temperatures. In low magnetic fields, B<0.2 mT, the NMR spectra show a pronounced low-frequency anomaly. Also, nonadiabatic response to a slowly varying magnetic field was observed. A rich phase diagram with three different nonparamagnetic regions is proposed. We estimate a critical spin temperature T(c) approximately 350 nK at B=0. We also report the absence of superconductivity in lithium at normal press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…On the other hand, other very recent experiments [6,7,8] have also shown that at this pressure range lithium presents a superconducting transition with T c ∼ 20K, becoming the highest transition temperature between simple elements [9]. It is noteworthy that experiments looking for superconductivity in lithium under ambient pressure have failed [10]. This even rises the interest to characterice the physical properties of compressed lithium close to the observed electronic and structural transitions.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, other very recent experiments [6,7,8] have also shown that at this pressure range lithium presents a superconducting transition with T c ∼ 20K, becoming the highest transition temperature between simple elements [9]. It is noteworthy that experiments looking for superconductivity in lithium under ambient pressure have failed [10]. This even rises the interest to characterice the physical properties of compressed lithium close to the observed electronic and structural transitions.…”
Section: Introductionmentioning
confidence: 94%
“…For example, recent experiments have shown that lithium superconducts at around 15 K when the applied pressure rises to 30 GPa [5][6][7], becoming the highest transition temperature for simple elements [8]. Experiments looking for superconductivity in lithium under ambient pressure have failed [9], which increases the interest in characterizing the physical properties of compressed light elements even more. On the other hand, interest in hydrogen has never been low.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] According to a recent x-ray analysis 3) lithium undergoes a bcc to fcc transition at 7.5 GPa, followed by a fcc to hR1 at 39 GPa and a hR1 to cI16 at around 40 GPa. On the other hand, despite experiments looking for superconductivity in lithium at equilibrium have failed, 8) it has been observed to superconduct at 20 K when pressure rises to 40 GPa. 9) This surprising and intriguing correlation between complex structures and superconductivity have rosed the interest to characterize physical properties of compressed lithium.…”
mentioning
confidence: 99%